2018
DOI: 10.1016/j.biomaterials.2017.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Clay nanoparticles for regenerative medicine and biomaterial design: A review of clay bioactivity

Abstract: Clay nanoparticles, composites and hydrogels are emerging as a new class of biomaterial with exciting potential for tissue engineering and regenerative medicine applications. Clay particles have been extensively explored in polymeric nanocomposites for self-assembly and enhanced mechanical properties as well as for their potential as drug delivery modifiers. In recent years, a cluster of studies have explored cellular interactions with clay nanoparticles alone or in combination with polymeric matrices. These p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
142
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 224 publications
(158 citation statements)
references
References 141 publications
(201 reference statements)
5
142
0
Order By: Relevance
“…In particular, Lap ‐containing hydrogels exhibited a significant decrease in degradation rate, which correlates with previous studies also reporting an enhanced Lap‐induced stability in polymers60 and biopolymers 45. We speculate that the suppressed hydrogel susceptibility to rapid enzymatic degradation observed in HA‐Tyr‐Lap and HA‐Tyr‐Lap‐GHK‐Cu 2+ may be attributed to the strong affinity of Lap discs to proteins and enzymes through physical adsorption,41 which would consequently limit hyaluronidase access to the HA backbone.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In particular, Lap ‐containing hydrogels exhibited a significant decrease in degradation rate, which correlates with previous studies also reporting an enhanced Lap‐induced stability in polymers60 and biopolymers 45. We speculate that the suppressed hydrogel susceptibility to rapid enzymatic degradation observed in HA‐Tyr‐Lap and HA‐Tyr‐Lap‐GHK‐Cu 2+ may be attributed to the strong affinity of Lap discs to proteins and enzymes through physical adsorption,41 which would consequently limit hyaluronidase access to the HA backbone.…”
Section: Resultssupporting
confidence: 89%
“…However, self‐assembling materials typically provide limited structural integrity, which has hindered their wide spread applicability. Lap is a 2D nanosilicate with anisotropic charge distribution, which has been exploited as an effective cross‐linker and rheology modifier for hydrogels39 for the delivery of drugs, growth factors, and antibodies 40,41. Lap has been reported to promote cell adhesion and proliferation and can exert osteogenic effects on cells in vitro 42.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer/clay nanocomposites including their 3D bioprinting have been reviewed recently for different biomedical applications. [ 19 ] Gaharwar et al [ 20 ] reviewed the potential of laponite nanoclay and its nanocomposites for additive manufacturing and regenerative medicine. Liu et al [ 21 ] reported an overview of halloysite nanotubes and respective nanocomposites for various biomedical applications such as drug delivery, biosensing, and bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Clays, a series of minerals with diverse dimensions, such as SiO 2 (0D), halloysite‐nanotubes (1D), montmorillonite (2D), and synthetic hectorite (2D), are extensively used as nanofillers in NC gels . One frequently used material is clay nanoplatelets, such as montmorillonite (MMT) and synthetic hectorite (laponite).…”
Section: Nps For Nanocomposite Hydrogelsmentioning
confidence: 99%
“…Each layer of the clay nanoplatelets consists of one octahedral sheet sandwiched by two tetrahedral sheets. The octahedral sheets usually contain cations, such as aluminum (Al) ions and magnesium (Mg) ions, which are octahedrally coordinated by oxygen, while the tetrahedral sheets consist of silicon dioxide with negative charges due to partial isomorphous substitution, typically of Al 3+ by Mg 2+ in montmorillonite and of Mg 2+ by Li + in laponite . The basal plane of these clay minerals has a permanent negative charge due to the isomorphous substitution of cations within the octahedral and/or tetrahedral layers by cations with lower valence.…”
Section: Nps For Nanocomposite Hydrogelsmentioning
confidence: 99%